Joe Noskiyi interview 1 - Noskiyi, Joe; Starr, David (Canadian Plains Research Centre, 1976)
6 p. transcript of an interview with Joe Noskiyi, conducted by David Starr on March 3, 1976. Tape number IH-311, transcript disc 40. This 72-year old gentleman talks about the area of land covered by trapper; and family connections between various northern settlements. Other no